Advancing biomedical applications: an in-depth analysis of silver nanoparticles in antimicrobial, anticancer, and wound healing roles - Jangid, Himanshu; Singh, Sudhakar; Kashyap, Piyush; Singh, Avtar; Kumar, Gaurav (Frontiers in Pharmacology, 2024)
This review offers a comprehensive examination of the scientific progression involving silver nanoparticles (AgNPs) within three key biomedical domains: their antimicrobial characteristics, potential for anticancer applications, and effectiveness in wound healing. By thoroughly analyzing literature spanning two decades, it evaluates the academic contributions, citation patterns, collaborative endeavors, and evolving subjects within each application field. The escalating number of publications focusing on the antimicrobial attributes of AgNPs underscores the global imperative to combat antibiotic resistance. In the domain of anticancer investigation, there has been a consistent advancement, concentrating on the cytotoxic impact of AgNPs and their ability to induce apoptosis in cancerous cells. Regarding wound healing, the incorporation of AgNPs into innovative dressings demonstrates their dual functionality in fostering tissue regeneration and averting infections. Examination of research output indicates that India and China lead in driving innovation, producing significant citations, thus underscoring the substantial impact and significance of their contributions worldwide. The review identifies enduring and emerging topics, such as the proliferation of "green synthesis" techniques in nanoparticle fabrication, illustrating the field's shift towards sustainability. The insights provided in this paper aim to guide and motivate current and future research endeavors, positioning silver nanoparticles as a crucial component in the advancement of next-generation medical interventions.